Assessing Sustainable Tourism in Top Selfie: A Mapping and Decision-Making Technique - Sasanti, Ika Alicia; Gravitiani, Evi; Sartika, Rebecca Cindy; Herniti, Dwi (ETIKONOMI, 2025)
Research Originality: This research paper combined literature on sustainable tourism, including the mapping and decision-making of tourism management in Top Selfie, Indonesia, towards sustainable tourism potential zones.Research Objectives: This study examined the impact of sustainable tourism patterns in the Top Selfie Pinusan area of Magelang, Indonesia, by considering various sustainability criteria.Research Methods: The researchers conducted comprehensive interviews with key stakeholders. The data was analyzed using ArcGIS to identify the development map of Top Selfie Pinusan and AHP analysis to policy recommendations for tourism development in Top Selfie Pinusan.Empirical Results: The research found that the location and potential of the Top Selfie Pinusan area make it a promising tourist destination when viewed from its development map. The AHP analysis showed that the eco-environmental criterion gave the highest weight to the water resources conservation sub-criterion. The alternative policy proposed in this research emphasized the promotion of alternative tourism.Implications: This research has important implications for the local government and tourism businesses, as they must address the challenge of creating tourist attractions aligned with the principles of sustainable tourism in Indonesia.JEL Classification: C1, Q510How to Cite:Sasanti, I. A., Gravitiani, E., Sartika, R. C., & Herniti, D. (2025). Assessing Sustainable Tourism in Top Selfie: A Mapping and Decision-Making Technique. Etikonomi, 24(1), 119 – 134. https://doi.org/10.15408/etk.v24i1.37947.